Principles of Creating Attractive Arcade Games with Original Examples - Emil MĄKA; Joanna WIŚNIEWSKA (Communications of International Proceedings, 2025)
In this work, we present some best practices in the development of arcade games. Creating computer games may be a profitable business. Additionally, it can be a job that is done with passion and commitment. We find that it is worth discussing about some recommended practices in this field.      We believe that it is good to treat game development as a project in which every detail must be considered – such as the target audience, the game’s objectives, rules, and graphic style. People who create computer games should also be aware of the basic animation principles to strive for perfection of their products and make the game aesthetic and eye-pleasing. In this paper, we also introduce the rules for creating game storylines and characterize some useful tool for programists to cope with working on such a large and multi-faceted project as creating your own computer game. Finally, we illustrate presented theory with an example of created arcade game.
Keywords: computer games; animation theory; graphical user interface; Unity